Management behind Room Cleaning of Luxury Hotels and Its Success and Balance Ratio - Ashish Sharma, Gaurav Khurana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This research examines the elements that influence room cleaning in the hotel industry, as well as the results of that training. The balance ratio and percentage of success rate of numerous hotels where skilled staff is involved behind room cleaning services are identified through survey results. Only task-related variables have a statistically significant impact on total cleaning time, according to the findings. Cleaning time is unaffected by any of the investigated employeerelated variables. Furthermore, three chores account for more than 3/4 of the overall cleaning time